ADAPTATION OF EDUCATION SYSTEM OF UKRAINE IN GLOBAL INFORMATIZATION CONDITIONS - Klochko O. (Kherson State University, 2018)
The problem of adaptation of higher education in Ukraine to the modern needs of the information society (knowledge society) is actual at this stage of the information society development. An alternative approach to choosing the strategies of Ukrainian higher education to the modern needs of the «knowledge society» has not been considered before. The purpose of our research is to choose the alternative strategies corresponding to this stage of information society development as an integral indicator - the vector of the dominant factors in adaptation of higher education in Ukraine to the modern needs of the «knowledge society». According to this problem, the integral indicator of human potential development is considered, one of the main characteristics of which are education levels and literacy. We find out the priorities of leading influences on it the indicators of education cost, education quality, the number of Internet users and users of mobile communication using the method of analysis of hierarchies. The hierarchical model with the purpose of obtaining priority criteria and finding alternative solutions that could be the basis for developing scenarios of Ukrainian higher education adaptation to the modern needs of the information society (knowledge society) has been constructed in the research. The alternative assessments, corresponding to this stage of the information society development, confirm the important influence of the quality of education and the use of Internet technologies in the educational process on the results of the adaptation of Ukrainian higher education to the modern needs of the «knowledge society».